Analysis of Topic Algae in Selected Natural History Textbooks - Brabcová, Blažena; Vodová, Libuše; Hvězdová, Kateřina (Scientia in educatione, 2018)
The study explored the way in which the topic Algae was presented in eight Natural History textbooks. The aim of the research was to find professional flaws in the curriculum dealing with Algae. The study deployed the content analysis method (Gavora, 2010, 2015). The identified flaws were divided into two categories – misclassification of Algae within the system of organisms and other professional flaws. These study identified 4 types of misclassification of Algae within the system of organisms and 61 other professional mistakes in total. The subsequent discussion compares the results of this study with the findings of other authors. The resulting synthesis is used by way of identifying the potential impact of the misinformation on the education of pupils. The article is supplemented by an appendix detailing the professional accuracy of the identified mistakes.